Walt Disney's Bambi. - Salten, Felix, 1869-1945.; Walt Disney Company (Danbury, Conn. : Grolier Enterprises, 1996)
The adventures of a young deer growing up in a forest.
Based on: Bambi, a life in the woods / by Felix Salten.
Keywords: Deer -- Juvenile fiction; Deer -- Fiction; Forest animals -- Fiction; Animals -- Fiction; Picture books